2021
DOI: 10.3390/ijerph182312751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Integrated Training on Balance and Ankle Reposition Sense in Ballet Dancers

Abstract: Objective: To investigate the effects of a 6-week integrated training program on the ankle joint reposition sense and postural stability in ballet dancers. Methods: Sixteen female ballet dancers participated in the study and underwent a 6-week integrated training program consisting of plyometric, proprioception and core stability exercises along with a home program involving additional ankle muscle strengthening and stretching. The ankle joint reposition tests and the parameters of the center of pressure (COP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, numerous studies have considered CMJ over a force platform as the gold standard to measure explosive strength in athletes [42,53]. Regarding the length of the training program, previous integrated CS and plyometric programs carried out with athletes reported results after interventions of 4-12 weeks [36,85]. We opted for an 8 week training program, as it is in the average CST length, and it has been suggested that the frequency and duration should be no less than twice a week over 4 weeks [61].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, numerous studies have considered CMJ over a force platform as the gold standard to measure explosive strength in athletes [42,53]. Regarding the length of the training program, previous integrated CS and plyometric programs carried out with athletes reported results after interventions of 4-12 weeks [36,85]. We opted for an 8 week training program, as it is in the average CST length, and it has been suggested that the frequency and duration should be no less than twice a week over 4 weeks [61].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that those who engaged in core stability work helped improve control of the ankle and serves as a potential avenue for managing patients with lateral ankle instability. 33,34 In addition, these findings also point to an interesting avenue for not only treatment and management but also potentially prevention of these injuries. 35 Particularly in athletic cohorts where the incidence is the highest, early intervention to work on dynamic strengthening and kinematics may be an important avenue for preventing new ALAIs and progression to CLAI.…”
Section: Managementmentioning
confidence: 96%
“…For example, ankle joints in soccer players experience intense physical demands during game sessions. Previous research has shown that core muscle strength training is one of the effective techniques to minimize the risk of injury and improve performance in various types of exercise [10][11][12].…”
Section: Introductionmentioning
confidence: 99%